Synthesis and characterization of bio-phenolic glyoxal resins via liquefaction and resinification of empty fruit bunch fibres - Ashmal Shahira, Ismail (2016)
The fast development of oil palm industry in the country has produced substantial amount of empty fruit bunch (EFB) fibres. These waste has caused pollution to the environment. To overcome this problem, research has been made to convert EFB into bio-phenolic resin which has beneficial uses in industry. This research describes the synthesis and characterization of bio-phenolic glyoxal resins by using liquefaction of EFB fibres. EFB were liquefied in phenol with the presence of hydrochloric acid and mixture of sulphuric acid with phosphuric acid as catalyst for 2 hours at 150 . The liquefied EFB and residue was characterized using FTIR to determine the functional groups present and to determine the effect of catalyst on phenol and EFB. Glyoxal is used as dialdehyde replacing formaldehyde for resinification as it is non-toxic and obtained from natural sources which make it environmental friendly. Next, after resinification process of liquefied EFB and glyoxal with the presence of sodium hydroxide, the bio-phenolic resin C and resin F were characterized using ATR-FTIR and TGA analysis. The ATR-FTIR analysis shows that resin C produced higher and strong intensity compared to resin F. TGA analysis were used to study the thermal stability and to compare the weight loss between those resins.The decomposition temperatures of sample F is 232.47 while the temperature of decomposition for resin C is 189.52 . It can be concluded that glyoxal can be a successful replacement for formaldehyde in producing Bio-Phenolic resin.